PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVINING PADA SMK NEGERI 1 PRAJEKAN KABUPATEN BONDOWOSO - Lestari, Layli Dwi; Arief, Mohammad Yahya; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Human resource management is part of organizational management that focuses on the elements of human resources. Employees as implementers in activities are required to have a good mental attitude, are dedicated, disciplined, and have good work performance. The purpose of this study was to analyze and examine the effect of work discipline on performance through job satisfaction. The population in this study were temporary employees (PTT) of SMK Negeri 1 Prajekan. The sampling technique used was saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS.3.0 application, show that work discipline has a significant positive effect on job satisfaction, work discipline has a positive effect on performance but is not significant, job satisfaction has a significant positive effect on performance, work discipline has an effect on performance through job satisfaction.